2016
DOI: 10.1177/1548051816655992
|View full text |Cite
|
Sign up to set email alerts
|

On Leading Meetings

Abstract: Leading meetings represent a typically and frequently performed leadership task. This study investigated the relationship between the leadership style of supervisors and employees' perception of meeting outcomes. Results showed that participants reported greater meeting satisfaction when their meeting leader was assessed as a considerate supervisor, with the relationship between considerate leadership style and meeting satisfaction being mediated by both relational-and task-oriented meeting procedures. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Inside the meeting, helpful leader behaviors include directing, structuring, contributing ideas and solutions, facilitating decisionmaking, and setting boundaries (Angouri & Marra, 2011;Lehmann-Willenbrock et al, 2015;Malouff et al, 2012;Pearson, 1989;van der Haar et al, 2017;Wodak et al, 2011). Research on followers' perceptions of meeting leadership points to the benefits of a considerate (Odermatt et al, 2016) and participative (Mroz et al, 2018a(Mroz et al, , 2018b leadership style, as well as a high-quality perceived leader-member exchange (Baran et al, 2012). Moreover, one study showed how perceived power distance and Leader member exchange (LMX) contribute to followers' emotional labor in meetings (Erks et al, 2017), suggesting that meeting leaders can play an influential role in managing employee well-being.…”
Section: Leadingmentioning
confidence: 99%
“…Inside the meeting, helpful leader behaviors include directing, structuring, contributing ideas and solutions, facilitating decisionmaking, and setting boundaries (Angouri & Marra, 2011;Lehmann-Willenbrock et al, 2015;Malouff et al, 2012;Pearson, 1989;van der Haar et al, 2017;Wodak et al, 2011). Research on followers' perceptions of meeting leadership points to the benefits of a considerate (Odermatt et al, 2016) and participative (Mroz et al, 2018a(Mroz et al, , 2018b leadership style, as well as a high-quality perceived leader-member exchange (Baran et al, 2012). Moreover, one study showed how perceived power distance and Leader member exchange (LMX) contribute to followers' emotional labor in meetings (Erks et al, 2017), suggesting that meeting leaders can play an influential role in managing employee well-being.…”
Section: Leadingmentioning
confidence: 99%
“…For instance, even though controlling the conversational floor (e.g., by assigning speaker turns and regulating topic progression) can contribute to more efficiency (Asmuß & Svennevig, 2009), it can also prevent people from expressing their opinions freely. Accordingly, research suggests that effective leaders take care not to overstructure their meetings (Van der Haar et al, 2017) and that it may be more important for leaders to show consideration during meetings (e.g., by identifying and addressing meeting attendees’ concerns) than to initiate structure (Odermatt et al, 2017). As a result, meeting leadership is likely to influence the occurrence of a MATM, such that high levels of initiating structure (without corresponding levels of consideration) result in unanswered questions and pent-up emotions, the combination of which triggers subsequent sensemaking processes.…”
Section: The Matm: An Affect-based Process Modelmentioning
confidence: 99%
“…Moreover, they are obliged to follow up on previous decisions and commitments. Unlike meetings in private organisations, which usually serve as a venue for accomplishing work-related goals (Odermatt et al 2017), this kind of meeting provides the means for displaying each actor's performance to others and involves image-building and other political behaviours. It requires a focus on the systematic progress of policy implementation, while also emphasising a shared approach to performance improvement through interaction within the network.…”
Section: Conduct Of Reformmentioning
confidence: 99%